Uji Eksperimental Fenomena Water Hammer dengan Variasi Ketinggian Surge Tower - Amrullah Mansyur; Muh Rusdi; Yiyin Klistafani (Politeknik Negeri Ujung Pandang, 2023)
In this study an analysis of the water hammer process was carried out in a piping installation with two pumps of different specifications arranged in a single arrangement. The solution given as a form of water hammer protection is variations in the height of the surge tower in piping installations. The aim of this research is to identify the phenomenon of water hammer in piping installations with different pump discharges and the effect of the height of the surge tower as a damper against pressure fluctuations that occur. The test is carried out by closing the valve suddenly and varying the height of the surge tower to determine the pressure value that occurs due to the water hammer effect. From the experimental test results, it can be seen that a surge tower with a height of 1 meter can best dampen back pressure due to the water hammer effect at a discharge of 2.4 m3/h. The theoretical and experimental analysis shows that the addition of a surge tower can reduce the pressure due to the water hammer effect. The pressure drop is 2.6 kg/cm2 to 2.2 kg/cm2 in pump installation 1 and the pressure drop is from 4.6 kg/cm2 to 1.8 kg/cm2 in pump installation 2. The use of a surge tower with a height of 1 meter can best reduce back pressure with 2.78 hours s at a discharge of 1.4 m3/h.